Pengaruh Partisipasi Anggaran dan Akuntansi Pertanggungjawaban terhadap Kinerja Manajerial - Agnes Shinta Dewi (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. Budget participation and accountability accounting are two important elements in the budgeting process because with these two elements that are effective, there will be efforts to achieve the targets that have been prepared so that good performance can be achieved with the aim to know and test empirically about the influence of budget participation and accounting accountability on managerial performance in Regional Owned Enterprises (BUMD) and to know and test the dominant variables affecting managerial performance in Regional Owned Enterprises (BUMD). Regional Owned Enterprises (BUMD) is the object of this study with a sample of 30 Top managers and Middle Managers using survey techniques with questionnaires. To answer the formulation, purpose and hypothesis of research, the analysis used is multiple linear regression analysis. The results of multiple linear regression analysis concluded that the 1st hypothesis that reads